2002
DOI: 10.1080/0144361021000020402
|View full text |Cite
|
Sign up to set email alerts
|

Retained placenta continues to be fatal but frequency can be reduced

Abstract: Retained placenta is potentially lift-threatening not only because of retention per se, but because of associated haemorrhage and infection as well as complications related to its removal. These risks are increased in women in poor social circumstances due to pre-existing malnutrition, anaemia and unsupervised home deliveries. The present study was undertaken to assess the situation in this rural area. A previous study at the same place suggested preventive strategies an and individualised approach. Incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…These risks are increased in women in poor social circumstances due to preexisting malnutrition, anemia and unsupervised home deliveries. [14] Among the indirect causes, anemia was found to be the major cause of maternal death in the present study. Our Þ ndings are consistent with those of other researchers who have reported that direct causes together with anemia are responsible for more than 65% of all maternal deaths in developing countries.…”
Section: Discussionmentioning
confidence: 87%
“…These risks are increased in women in poor social circumstances due to preexisting malnutrition, anemia and unsupervised home deliveries. [14] Among the indirect causes, anemia was found to be the major cause of maternal death in the present study. Our Þ ndings are consistent with those of other researchers who have reported that direct causes together with anemia are responsible for more than 65% of all maternal deaths in developing countries.…”
Section: Discussionmentioning
confidence: 87%
“…In a study by Chhabra et al 10 in Kasturba Hospital, Delhi, it was found that incidence of retained placenta was 0.23% of all births over 15 years. In their study, out of four deaths two women delivered at nearby district hospital and were referred moribund and died.…”
Section: Discussionmentioning
confidence: 99%
“…Shaarawy et al who have evaluated the clinical value of microtransfferrinuria and microalbuminuria in prediction of preeclampsia in asymptomatic women have concluded that microtransfferrinuria was a more sensitive marker than microalbuminuria [33]. However, Chhabra et al have found that estimation of microalbuminuria around 18 weeks of gestation seemed useful, especially in primigravida [34,35].…”
Section: Discussionmentioning
confidence: 97%